Does financial performance and company age affect the rating Islamic bond? - Siti Komariyah; Firdha Rahmiyanti; Nurul Hadi Manan (Universitas Islam Negeri (UIN) Walisongo Semarang, 2022)
Purpose - This study aims to determine the effect of solvency ratios, liquidity ratios, profitability ratios, and company age on the rating of Islamic bonds (Sukuk) in companies issuing Sukuk listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. The independent variables used in this study are solvency ratio (DER), liquidity ratio (CR), profitability ratio (ROE), and company age. The dependent variable is the rating of Sukuk.Method - This study uses quantitative research methodology by purposive sampling. The gathered data on this study were procesed using STATA v.14.Result - The results showed that the solvency ratio had no negative effect on the rating of Sukuk, the liquidity ratio had a positive effect on the rating of Sukuk, the profitability ratio has a negative effect on the rating of Sukuk, company age has a positive effect on the rating of Sukuk.Implication - Future research can expand the object of research in several other districts and can add research variables.Originality - The sluggish global economic condition that has resulted in a decline in the performance of sukuk issuing companies is an interesting topic to study. In addition, the analysis tool uses several panel data models as a new thing in this study.